Advances in the knowledge of Echinoparyphium megacirrus and Echinostoma sp. (Digenea: Echinostomatidae) parasites of Diplodon chilensis (Pelecypoda) in Patagonia (Argentina) - Flores, Verónica (2016)
Diplodon chilensis (Pelecypoda, Hyriidae) is the only species present in the Patagonian Region of the Neotropical endemic genus Diplodon. Metacercariae of genera Echinostoma and Echinoparyphium have been found in this bivalve species and in the snail Lymnaea viatrix. The aim of this work was to evaluate the characteristics of the infestations and the geographic distribution of Echinoparyphium megacirrus and Echinostoma sp., parasites of D. chilensis in Andean-Patagonian environments and to advance in the knowledge Echinostoma sp. A total of 19 environments (39°06’S - 42°36’S) were sampled in order to collect specimens of D. chilensis to record the presence of metacercariae and to perform experimental infestations in Gallus gallus domesticus with parasitized viscera. The distribution range of E. megacirrus and Echinostoma sp. was determined by the study of metacercariae in natural environments, and by experimental ovigerous adults obtained in infestations with G.g. domesticus. Both species of Echinostomatidae were located mainly in the pericardial cavity, and in hepatopancreas and, gonads of the moluscan host. The measurements and morphology of the metacercariae and adults of E. megacirrus coincide with those of the original description. For Echinostoma sp. metacercariae, diameter and thickness of cyst wall, and size and distribution of the crown spines are different from those previously described in D. chilensis. It is the first time that ovigerous specimens of Echinostoma from experimental infestations were obtained, indicating that D. chilensis is a suitable secondary host for this digenean species. Comparisons of morphology and measurements of the experimental adults obtained with other species of Echinostoma with 37 spines collar, would assign them to Echinostoma chloephagae previously described in the native Chloephaga picta leucoptera, although the spines in our specimens are smaller. Comparing the presence and infestation values of both metacercariae, E. megacirrus has a wider distribution range, is recorded in more environments and presents higher prevalences.